(untitled) (MAUSAM, 1984)
Hindcast wave heights in Bay of Bengal for summer monsoon are presented using 5MB method and wind data reported in Indian Daily Weather Reports during 1976-80. Monthly average significant wave heights of both sea and swell range between 0.5 and 2.0 In. Southern and central portions of Bay are associated with higher waves. Propagation of swells in northerly direction has been observed during the period June-August. Highest possible significant wave heights computed from maximum wind speeds reported, vary from 2.5 to 6.5 m.